Pengaruh Lingkungan Kerja Dan Semangat Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Pos Indonesia (PERSERO) Pamekasan) - Runik Puji Rahayu; Alfi Hasaniyah; Citra Larashati Surya (Assyarikah: Journal of Islamic Economic Business, 2022)
PT. Pos Indonesia (Persero) Pamekasan which is located at Jl. Mesigit No.3, Rw. 04 is a state-owned enterprise that aims to participate in implementing and supporting Government policies & programs in the field of economy and national development in general and in particular in the field of postal and giro services for communities both within and outside the territory of Indonesia by applying the principles of limited liability companies. The approach used in this study is a survey approach. The survey method is a research method that studies data from samples taken from a population to generalize and use questionnaires as a data collection tool. The results showed, 1) simultaneously showed that the working environment variable (X1) and work spirit (X2) simultaneously had an effect on employee performance by 0.761 or 76.1% while the rest (100% -76.1%= 23.9% ) influenced by other factors examined in this study. 2) partially shows that the working environment variable (X1) partially influences employee performance by having tcount> ttable which is 8,779> 2,009. 3) partially shows that the work spirit variable (X2) partially influences employee performance by having tcount> ttable which is 3,330> 2,009. 4) The most dominant variable influencing employee performance is the work environment (X1). The value of t is greater by having tcount> ttable which is 8,779> 2,009.